The role of the microbiota-gut-brain axis and intestinal microbiome dysregulation in Parkinson’s disease - Li, Qing; Meng, Ling-bing; Chen, Li-jun; Shi, Xia; Tu, Ling; Zhou, Qi; Yu, Jin-long; Liao, Xin; Zeng, Yuan; Yuan, Qiao-ying (Frontiers in Neurology, 2023)
Parkinson’s disease (PD) is a complex progressive neurodegenerative disease associated with aging. Its main pathological feature is the degeneration and loss of dopaminergic neurons related to the misfolding and aggregation of α-synuclein. The pathogenesis of PD has not yet been fully elucidated, and its occurrence and development process are closely related to the microbiota-gut-brain axis. Dysregulation of intestinal microbiota may promote the damage of the intestinal epithelial barrier, intestinal inflammation, and the upward diffusion of phosphorylated α-synuclein from the enteric nervous system (ENS) to the brain in susceptible individuals and further lead to gastrointestinal dysfunction, neuroinflammation, and neurodegeneration of the central nervous system (CNS) through the disordered microbiota-gut-brain axis. The present review aimed to summarize recent advancements in studies focusing on the role of the microbiota-gut-brain axis in the pathogenesis of PD, especially the mechanism of intestinal microbiome dysregulation, intestinal inflammation, and gastrointestinal dysfunction in PD. Maintaining or restoring homeostasis in the gut microenvironment by targeting the gut microbiome may provide future direction for the development of new biomarkers for early diagnosis of PD and therapeutic strategies to slow disease progression.